Local multipoint distribution services architecture based on rain profile extracted from meteorological radar - Kusay Faisal A. Al-Tabatabaie, 1977-; Jafri Din; Nor Hisham Khamis, 1965-; Fakulti Kejuruteraan Elektrik (2013)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2013